Calligraphy writing device convenient to clean - ZHANG XINGZI; CAO MENGBO; MAO YALIN (2023)
The utility model discloses a calligraphy writing device convenient to clean, which belongs to the technical field of calligraphy practice and comprises a penholder, a control cylinder is arranged on the upper surface of the penholder, a push block is clamped on the upper surface of the control cylinder, a transmission cylinder is arranged in the control cylinder, and the lower surface of the push block is fixedly connected with the upper surface of the transmission cylinder. According to the calligraphy writing device convenient to clean, the pen holder and the sliding block are arranged to drive the transmission rod to rotate and the pen holder and the pen point to rotate, after the push block is loosened, the first check block and the transmission cylinder are pushed upwards under the elastic force action of the first spring in cooperation with the second check block, and at the moment, the sliding block is stressed to reversely rotate along the guide groove; according to the mode, the push block is presse